2020
DOI: 10.3233/jad-190828
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Criteria for Psychosis in Alzheimer’s Disease and Related Dementias: Toward Better Phenotypic Classification and Biomarker Research

Abstract: Background: Psychotic symptoms are common in Alzheimer's disease (AD) and related neurodegenerative disorders and are associated with more rapid disease progression and increased mortality. It is unclear to what degree existing criteria are utilized in clinical research and practice. Objective: To establish research criteria for the diagnosis of psychosis in AD. Methods: The International Society to Advance Alzheimer's Research and Treatment (ISTAART) Neuropsychiatric Symptoms (NPS) Professional Interest Area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 98 publications
2
72
0
Order By: Relevance
“…Potentially, the future diagnostic criteria of late-life psychotic disorders may also incorporate the newer biomarkers of dementia (such as those related to amyloid protein, tau protein, and neuronal injury) [10] to definitively exclude underlying neurodegenerative processes, especially when these biomarkers become more accessible to general clinicians in the foreseeable future. Such approach is not inconsistent with the direction taken by the recently proposed consensus criteria for psychosis in Alzheimer's disease [64], where there is an increasing emphasis that late-life psychotic disorders may potentially be manifestations of preclinical and prodromal Alzheimer's disease.…”
Section: Potential Implications Of the Findingsmentioning
confidence: 99%
“…Potentially, the future diagnostic criteria of late-life psychotic disorders may also incorporate the newer biomarkers of dementia (such as those related to amyloid protein, tau protein, and neuronal injury) [10] to definitively exclude underlying neurodegenerative processes, especially when these biomarkers become more accessible to general clinicians in the foreseeable future. Such approach is not inconsistent with the direction taken by the recently proposed consensus criteria for psychosis in Alzheimer's disease [64], where there is an increasing emphasis that late-life psychotic disorders may potentially be manifestations of preclinical and prodromal Alzheimer's disease.…”
Section: Potential Implications Of the Findingsmentioning
confidence: 99%
“…Another classification for neuropsychiatric symptoms in AD was proposed by Ismail et al [22] who classified these symptoms into five categories: drive and motivation, emotional dysregulation, impulsivity, social inappropriateness, and abnormal perceptions or thoughts. To overcome the classification limitation of neuropsychiatric symptoms in AD, Fischer et al [23] suggested that any classification system should address their overlap with related conditions (especially, regarding agitation), recognize that symptoms may emerge in the preclinical and prodromal phases, and add a more specific differentiation between delusions and hallucinations. Regardless of their classification, neuropsychiatric symptoms in AD have been captured by the Neuropsychiatric Inventory-Questionnaire (NPIQ) [24] for decades.…”
mentioning
confidence: 99%
“…Another challenge has been the under‐recognition of behavioral symptoms of NCDs, partly due to variability in terminology and criteria used to describe these symptoms 81–83 . Recent work has addressed these issues by clarifying the nosological issues and criteria for diagnosis of behavioral syndromes throughout the spectrum of NCDs 82 .…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge has been the under‐recognition of behavioral symptoms of NCDs, partly due to variability in terminology and criteria used to describe these symptoms 81–83 . Recent work has addressed these issues by clarifying the nosological issues and criteria for diagnosis of behavioral syndromes throughout the spectrum of NCDs 82 . Use of informant‐based tools described in this review may further standardize the assessment and management of behavioral symptoms that is particularly important during the current pandemic and beyond due to unique vulnerabilities of this population 84 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation